In silico approach towards lipase mediated chemoenzymatic synthesis of (S)-ranolazine, as an anti-anginal drug. Issue 54 (18th May 2016) - Sawant, Ganesh; Ghosh, Saptarshi; Banesh, Sooram; Bhaumik, Jayeeta; Chand Banerjee, Uttam
Abstract : An in silico modelling based biocatalytic approach for the synthesis of drugs and drug intermediates in enantiopure forms is a rationalized methodology over the organo-chemical routes. Abstract : An in silico modelling based biocatalytic approach for the synthesis of drugs and drug intermediates in enantiopure forms is a rationalized methodology over the organo-chemical routes. In this study, enzyme-ligand based docking was carried out using ( RS )-ranolazine, as the model drug for the screening of a suitable biocatalyst for the kinetic resolution of the racemic drug. The differential interaction of the two enantiomers with the lipase was analyzed on the basis of docking score and H-bond interaction with the amino acid residues, which helped to define the trans -esterification mechanism. Ranolazine [ N -(2, 6-dimethylphenyl)-2-[4-(2-hydroxy)-3-(2-methoxyphenoxy)propylpiperazin-1-yl]acetamide], an anti-anginal drug, significantly reduces the frequency of anginal attack and has also been used for the treatment of ventricular arrhythmias, and bradycardia. Various lipases were examined via computational as well as wet lab screening and Candida antartica lipase in the form of CLEA was the most efficient one for the ( S )-selective kinetic resolution of ( RS )-ranolazine, with highest conversion and enantiomeric excess. This is the first report of the chemo-enzymatic synthesis of ( S )-ranolazine where the whole drug molecule was used for lipase catalysis. The present study showed that the combination of in silico studies and a classical wet lab approach could change the paradigm of biocatalysis.